POSTURE ANALYSIS APBD AND EDUCATION APBD IN KOTA KUPANG - Habaora, Fellyanus (Jurnal Penelitian Kebijakan Pendidikan, 2019)
This research uses an ex post facto design because researchers only took data from the Education Budget from in 2013-2019 which was subsequently concluded to be a conclusion. This research uses data collection with documentation techniques. Information can be obtained through facts stored in the form of documents. This research was conducted for 6 months, namely January-June 2019. Posture of APBD in Kota Kupang shows two different paradigms, namely the period 2013-2016 shows the proportion for indirect expenditure (apparatus expenditure) is higher than direct expenditure (expenditure for the public), while the 2017-2019 period shows that direct expenditure on society is greater than indirect expenditure for apparatus. Then the posture APBD of Education for the period 2013-2017 shows that alignments government to expenditure public are still very weak because indirect expenditure is greater than direct expenditure, but the period 2013-2017 showed a significant increase in direct expenditure compared to indirect expenditure. Likewise, the commitment of Kota Kupang Government to the implementation of the National Education System Law shows that the support Kota Kupang Government in the 2013-2017 period against the provisions Law tends to weaken because of the proportion of the education budget from the total APBD in decreased significantly from 42.36% to 25.75%. While the 2017-2019 period shows the existence of the government's partiality towards the world of education where Kota Kupang Government in addition to increasing the direct expenditure budget that oriented to reduce the burden on the households of its population also increases the education budget posture from 25.75% to 29.56%. In general, factors of leadership and commitment to development of public welfare have more influence on the preparation of budget postures in APBD Kota Kupang.